Effect of paraquat on cellular defense enzymes and glutathione level of Funalia trogii - Asma, D; Yeşilada, O (Folia microbiologica, 2002)
The effect of paraquat on the activities of antioxidant defense and detoxifying enzymes of the white-rot fungus Funalia trogii was determined. Paraquat increased the activities of glutathione reductase (GR), glutathione transferase (GT) and superoxide dismutase at 1 mmol/L, while at 0.1 mmol/L it did not affect the activity of GR and GT. It depressed the catalase activity and the amount of glutathione at all concentrations used. Paraquat treatment probably depresses antioxidant defense components such as catalase and glutathione.
Keywords: kinetika; paraquat; superoxiddismutasa; glutathionreduktasa; Antioxidants; Glutathione; glutathiontransferasa; Glutathione Transferase; antioxidancia; Superoxide Dismutase; herbicidy; katalasa; glutathion; Kinetics; Polyporales; Catalase; Glutathione Reductase; Herbicides; Paraquat